Quality Management Workshop: Feedback on ISO Certification in a Pharmaceutical Technology Unit - Perriat Sophie; Cretu Yann; Canonge Jean-Marie; Puisset Florent (De Gruyter, 2017)
The implementation of a quality management system within a PUI is an integral part of the tasks of a pharmacist and a pharmacy technician. In this workshop we proposed to share our ISO 9001 certified unit experience. We encouraged participants to share about their interest in a quality management system and gave them some keys for facilitating the initiation of an ISO 9001 certification.